The Peaceful Resolution of International Disputes – Negotiations as a Model - Silini, Mohamed Sghir (Journal of Legal Studies and Researches, 2020)
Since the end of the last century, the efforts of peace-loving politicians have tended to replace peaceful means instead of the force in settling the international disputes. For this purpose, major conferences such as the Hague Conference of 1899 and 1907 were held, in which a set of provisions for the peaceful settlement of international disputes was decided, and then added to these. The other provisions of the League of Nations, the agreements concluded under it and the Charter of the United Nations. Peaceful ways of settling the international disputes are two levels, amicable ways, the first thing that states have to resort to settle their differences, and unfriendly ways, or methods of coercion , that might be used by the state if the first means fail, and among Peaceful ways is the negotiations. So what is the concept of negotiations and what is Its role in resolving international conflicts?